Dimensions of Conservation: Exploring Differences Among Energy Behaviors. (May 2014) - Karlin, Beth; Davis, Nora; Sanguinetti, Angela; Gamble, Kristen; Kirkby, David; Stokols, Daniel
Residential energy conservation is among the most efficient means of reducing emissions, yet behavior is lagging behind this potential, suggesting this is an area where psychology can contribute. Research suggests that conservation behaviors may cluster into distinct dimensions, and a greater understanding of these differences could improve intervention. This article explores this idea through systematic literature review and analysis of survey data. Content analysis of 28 articles showed strong support for two primary dimensions (curtailment and efficiency), with up to nine defining attributes. However, analysis also identified inconsistencies, leaving questions about their validity. Factor analysis of survey data identified two principal components along these dimensions; subsequent analyses revealed several differences in their predictors. Results provide support for a dimensional approach and suggest further research into underlying attributes. Although the curtailment versus efficiency dichotomy may be useful, it also has the potential to obscure high leverage maintenance behaviors, especially for renters.